Personal Trainer: A look at the Management of the Quality of the Services provided - Thiago Seixas dos Santos; Jefferson Veira Silva de França (Universidade Salgado de Oliveira, 2020)
This study aimed to highlight the main features of Personal Trainer's services located in Caruaru. It is a descriptive, transversal study that had as a research tool a semi-structured questionnaire with questions regarding Personal Trainer service. Participated in this study customers of twenty professionals, corresponding to five gyms strategically located to better represent the target of púplico research. The survey was composed of 155 people aged between 18 and 70 years and an average of 30.2 9.5. It was observed that the appearance and physical form of the personal are fundamental attributes. It was noticed that the professional has to be updated, as well as achieve the results of their customers. Also notes that the personals offer information of interest to its customers related to physical exercise in social networks. So, I got to have some characteristics of personal trainers of Caruaru, waiting, result in a better quality of services provided by these professionals in the search for better service and the satisfaction of its customers. Keywords: Personal Trainer; Service Quality; Sports Marketing.